Impact of Intellectual Capital Management and Human Capital Circulation on Business Practice at Macro- and Micro Level - Oleynikova, Iryna; Balabaniuk, Zhanna (Information Management and Business Review, 2017)
Nowadays the main potential for growth comes from the ability to innovate and succeed with breakthrough ideas. However, despite growing importance of the subject matter, there are still no standard practices that would perform such a measurement and employ tendencies of human capital circulation. Various attempts have been made over recent years, but none have achieved general acceptance among experts in the business field. Although there is no universally accepted theory, each has its own strengths and weaknesses in the deriving approximate value of intellectual capital for various companies. In this work, we looked over some theories that have been suggested to estimate intellectual capital and analyzed data from Ukrainian IT companies in order to prove how important measurement of intellectual capital and human capital circulation trends to allow for much better representation of an organization’s competitive position. Additionally, the impact of intellectual capital on various Key Performance Indicators, such as Economic Value Added and Weighted Average Cost of Capital, was examined with supporting financial analysis performed. The paper concludes with an overview of methodological and managerial implications of the research, theoretical and practical limitations and possible improvements, and considerations for further research in the field of study.